Stock Valuation Using the PER (Price to Earnings Ratio) and the PBV (Price to Book Value) Methods (Case Study of PT Cikarang Listrindo Tbk., Whose Share is Listed on the Indonesian Stock Exchange) - Fitrah Diraya Sutardi; Kekey M. Deva; Dharma Adita; Ruth S. H. Siahaan; Gusganda Suria Manda (Jurnal Ilmiah Wahana Pendidikan, 2026)
Entering the fourth quarter of 2025, investments in bonds and deposits are considered less satisfactory by investors due to low returns resulting from interest rate cuts by Bank Indonesia. Consequently, alternative investments such as stocks are once again being explored by investors and are deemed capable of providing higher returns. Investors looking to invest in stocks must conduct a valuation to determine the position and value of the company's shares they intend to purchase. The purpose of this study is to determine whether POWR stock is overvalued, fairly valued, or undervalued by using the Price to Earnings Ratio (PER) and Price to Book Value (PBV) valuation methods. Furthermore, this study is expected to provide information that will assist stock investors in making their investment decisions. The analysis results in this study indicate that stock valuation using the PER method fluctuates and is in an overvalued position. The POWR stock position calculated using the PBV method shows an average valuation of 1.44 times and is also in an overvalued position. Stock investors should consider selling POWR stock based on the PER and PBV stock valuation methods.